2007
DOI: 10.1002/jbm.a.31750
|View full text |Cite
|
Sign up to set email alerts
|

The artificial surface‐induced whole blood inflammatory reaction revealed by increases in a series of chemokines and growth factors is largely complement dependent

Abstract: Exposing blood to an artificial surface results in a systemic inflammatory response, including cytokine release and complement activation. We studied the artificial surface-induced inflammation in human whole blood using an extensive panel of inflammatory mediators including proinflammatory cytokines, chemokines and growth-factors and investigated the role of the complement system in the induction of this response. Using multiplex technology, 27 different inflammatory mediators were measured after circulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 19 publications
2
27
2
1
Order By: Relevance
“…Our results demonstrated that both C3a and C5a are major contributors to the release of pro-inflammatory cytokines, since both inhibition of C3 and C5 as well as C3aR and 25 Furthermore, a complete dependency on complement has previously also been found for the inflammatory cytokines IL-1β, TNF, IL-6, IL-8, MIP-1β and MCP-1 during exposure to poly-l-lysine containing microcapsules. 18 To the best of our knowledge, this is the first study that showed that engineered nanoparticles, like IONPs, induce cytokine secretion in a complementdependent manner, thus underscoring the potential of inhibiting complement to prevent detrimental coagulation-and inflammation-related effects induced by nanoparticles.…”
Section: Discussionsupporting
confidence: 72%
“…Our results demonstrated that both C3a and C5a are major contributors to the release of pro-inflammatory cytokines, since both inhibition of C3 and C5 as well as C3aR and 25 Furthermore, a complete dependency on complement has previously also been found for the inflammatory cytokines IL-1β, TNF, IL-6, IL-8, MIP-1β and MCP-1 during exposure to poly-l-lysine containing microcapsules. 18 To the best of our knowledge, this is the first study that showed that engineered nanoparticles, like IONPs, induce cytokine secretion in a complementdependent manner, thus underscoring the potential of inhibiting complement to prevent detrimental coagulation-and inflammation-related effects induced by nanoparticles.…”
Section: Discussionsupporting
confidence: 72%
“…The activation of the complement system is one of the most significant challenges when blood is exposed to foreign materials 16, 17, 18, 19. Measures of C3a and SC5b‐9, also called Terminal Complement Complex (TCC), are widely used as complement activation markers.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, C3 is found in the peritoneal fluid [8] as well as in subcutaneous and omental adipose tissue [9]. C3 is a contributor to the biomaterial-induced inflammation during blood contact [10], and recently C3 was demonstrated to be involved in the inflammatory host response against subcutaneous and intraperitoneally implanted…”
Section: Introductionmentioning
confidence: 99%